INTERACTION OF ESTROGEN AND PROGESTERONE IN CHICK OVIDUCT DEVELOPMENT : II. Effects of Estrogen and Progesterone on Tubular Gland Cell Function - Oka, Takami (The Rockefeller University Press, 1969)
The effects of estrogen and progesterone on the function of chick oviduct tubular gland cells have been studied. Such function, as measured by the increase in specific cell products such as lysozyme and ovalbumin, requires the continuous presence of estrogen or progesterone. Withdrawal of hormone results in a rapid cessation of function and an involution of the oviduct accompanied by rapid decreases in total weight, lysozyme, and RNA. During such involution, tubular gland cells per se persist, as evidenced by a lack of comparable decrease in total DNA content and by histological demonstration of tubular gland cells. When estrogen administration is reinstituted, preexisting tubular gland cells rapidly synthesize ovalbumin and lysozyme without requiring new DNA synthesis. Administration of progesterone also stimulates the function of such cells. Furthermore, the effects of estrogen and progesterone are synergistic on the synthesis of lysozyme and ovalbumin, whereas progesterone antagonizes the estrogen-evoked formation of tubular gland cells. It is suggested that such complex interactions of estrogen and progesterone on oviduct development and function result from differences in responsiveness of the various cell types present in the tissue.